How young adults with autism spectrum disorder watch and interpret pragmatically complex scenes. Issue 11 (2nd November 2017) - Lönnqvist, Linda; Loukusa, Soile; Hurtig, Tuula; Mäkinen, Leena; Siipo, Antti; Väyrynen, Eero; Palo, Pertti; Laukka, Seppo; Mämmelä, Laura; Mattila, Marja-Leena; Ebeling, Hanna
ABSTRACT: The aim of the current study was to investigate subtle characteristics of social perception and interpretation in high-functioning individuals with autism spectrum disorders (ASDs), and to study the relation between watching and interpreting. As a novelty, we used an approach that combined moment-by-moment eye tracking and verbal assessment. Sixteen young adults with ASD and 16 neurotypical control participants watched a video depicting a complex communication situation while their eye movements were tracked. The participants also completed a verbal task with questions related to the pragmatic content of the video. We compared verbal task scores and eye movements between groups, and assessed correlations between task performance and eye movements. Individuals with ASD had more difficulty than the controls in interpreting the video, and during two short moments there were significant group differences in eye movements. Additionally, we found significant correlations between verbal task scores and moment-level eye movement in the ASD group, but not among the controls. We concluded that participants with ASD had slight difficulties in understanding the pragmatic content of the video stimulus and attending to social cues, and that the connection between pragmatic understanding and eye movements was more pronounced for participants with ASD than for neurotypical participants.